A ribonucleopeptide world at the origin of life. Issue 1 (7th November 2017) - Saad, Nizar Y.
Abstract: The structural flexibility of RNA and its ability to store genetic information has led scientists to postulate that RNA could be the key molecule for the development of life on Earth, further leading to formulate the RNA world hypothesis that received a lot of success and acceptance after the discoveries of the last thirty‐five years. Despite its highly structural and functional significance, the difficulty in synthesizing the four nucleobases that form the RNA polymer from the same primordial soup, its low stability, and limited catalytic repertoire, make the RNA world hypothesis less convincing even though it remains the best explanation for the origin of life. An increasing number of scientists are becoming more supportive of a more realistic approach explaining the appearance of life. In this review, I propose an enhanced explanation for the appearance of life supported by recent discoveries and theories. Accordingly, amino acids and peptides associated with RNA (e.g., ribonucleopeptides) might have existed at the onset of RNA and might have played an important role in the continuous development of self‐sustaining biological systems. Therefore, in this review, I cover the most recent and relevant scientific investigations that propose a better understanding of the ribonucleopeptide world hypothesis and the appearance of life. Finally, I propose two hypotheses for a primitive translation machinery (PTM) that might have been formed of either a T box ribozyme or a ribopolymerase.